1989
DOI: 10.1128/mcb.9.10.4220
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in the anticodon stem affect removal of introns from pre-tRNA in Saccharomyces cerevisiae.

Abstract: To evaluate the role of exon domains in tRNA splicing, the anti-codon stem of proline pre-tRNAUGG from Saccharomyces cerevisiae was altered by site-directed mutagenesis of the suJ8 gene. Sixteen alleles were constructed that encode mutant pre-tRNAs containing all possible base combinations in the last base pair of the anticodon stem adjacent to the anticodon loop (positions 31 and 39). The altered pre-tRNAs were screened by using an in vitro endonucleolytic cleavage assay to determine whether perturbations in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
18
0

Year Published

1989
1989
2009
2009

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 25 publications
1
18
0
Order By: Relevance
“…luevis (Mattoccia et al, 1988), HeLa cells (Filipowicz and Shatkin, 1983), wheat germ (Stange et al, 1988) and in the archaebacterium Halobacterium volcanii (Thompson and Daniels, 1988). The HeLa and Xenopus endonucleases were shown to excise introns from quite a number of heterologous pre-tRNA species.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…luevis (Mattoccia et al, 1988), HeLa cells (Filipowicz and Shatkin, 1983), wheat germ (Stange et al, 1988) and in the archaebacterium Halobacterium volcanii (Thompson and Daniels, 1988). The HeLa and Xenopus endonucleases were shown to excise introns from quite a number of heterologous pre-tRNA species.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that Xenopus and mammalian splicing endonucleases are capable of excising introns from heterologous pre-tRNA species (Melton et al, 1980;Standring et al, 1981;Filipowicz and Shatkin, 1983;van To1 et al, 1987;Mattoccia et al, 1988). Little information exists about the species specificity of the yeast splicing endonuclease until now.…”
Section: Plant and Vertebrate Intron-containing Trna Precursors Are Ementioning
confidence: 99%
See 3 more Smart Citations